E-Commerce Trends in Tiruchirappalli. - Karthiga, B.; Sujatha, V. (International Journal of Psychosocial Rehabilitation, 2020)
E-commerce stands for electronic commerce and pertains to trading in goods and services through the electronic medium. India is showing tremendous growth in the e-commerce. i.e. the Internet or phone. On the Internet, it pertains to a website, which sells products or services directly from the site using a shopping cart or shopping basket system and allows credit card payments. It involves conducting business with the help of the electronic media, making use of the information technology such as Electronic Data Interchange (EDI).